Investigation of Highpower Distributed Feedback diode lasers with ultra-narrow linewidth - Nguyen, Thanh Phuong (Old Journal, 2018)
High power diode lasers emitting at near infrared have many important applications because of their compactness, high energy-conversion efficiency and their reliability. Some high-accuracy applications such as: atomic clock, atomic absorption... require lasers with narrow linewidth at high output power. Therefore, measuring linewidth of the lasers is very necessary. In this report, techniques to characterize ultra-narrow linewidth laser are shown. Base on these technique, semiconductor 780 nm DFB laser is investigated having linewidth of 19 KHz at 250 mW output power and 25°C.